An improvised life : a memoir - Arkin, Alan (Da Capo Press, 2011)
"An Improvised Life" is Oscar winner Alan Arkin's wise and unpretentious recollection of the process--artistic and personal--of becoming an actor, and a revealing look into the creative mind of one of the best practitioners on stage or screen.